Endometrial receptivity in women of reproductive age with "thin" and "absolutely thin" endometrium - Natalia V. Aganezova; Sergey S. Aganezov; Ksenia E. Gogichashvili (IP Berlin A.V., 2023)
Aim. To evaluate the expression of steroid receptors (estrogen [ER] and progesterone [PR]) in the endometrium during the implantation window in females with a history of fertility disorders in "thin" and "absolutely thin" endometrium versus healthy females. Materials and methods. A prospective comparative study was conducted. The study group (n=42) included patients with "thin" endometrium (7 mm M-echo 5 mm at cycle days 1113 according to ultrasound); the comparison group (n=10) included females with "absolutely thin" (5 mm according to ultrasound in the pre-ovulatory days) endometrium (females in both groups had a history of infertility and miscarriage of unclear reasons in the anamnesis); the control group included 16 healthy fertile females. A Pipelle biopsy of the uterine mucosa was performed on day 68 after ovulation, and a peripheral blood sample was obtained to measure the concentration of sex steroids (estradiol [E2] and progesterone [P]). Endometrial samples were examined by histological and immunohistochemical methods (ER, PR expression). Results. All study participants had an ovulatory cycle of P16.1 nmol/L (day 68 after ovulation) and normal estrogen levels (E2, pmol/L). E2/P was similar in all cohorts (p0.05 for all measures). ER and PR expression in the endometrium similar to those in healthy females was detected in 20% of patients in the study and comparison groups (M-echo = 4.83.1 mm): 21% (9/42) and 20% (2/10), respectively. ER and PR expression in the endometrial glands and ER expression in the endometrial stroma were significantly different (p0.05) from healthy females in 79% (41/52) of patients with "thin" endometrium and 80% (8/10) of patients with "absolutely thin" endometrium. No differences in the ER or PR expression in the endometrium in females with hypoplastic endometrium were found (p0.05). Conclusion. The M-echo value does not accurately determine endometrial hormonal-receptor abnormalities: 20% of the study participants with hypoplastic endometrium had ER and PR expression comparable to those in healthy females. No differences were found in the expression of endometrial estrogen and progesterone receptors in females with "thin" and "absolutely thin" endometrium.